2017
DOI: 10.1007/s00779-017-1027-z
|View full text |Cite
|
Sign up to set email alerts
|

Contributing or receiving-the role of social interaction styles in persuasion over a social networking platform

Abstract: In this paper, the use of the social network platform Twitter is explored in relation to behavior change (BC) for health. We studied the effect of participation style (tweeters vs. non-tweeters) on perceived health behavior change through the constructs "social influence," "efficacy," and "pre-test health behavior." In the experiment (N = 30), participants were given a basic health message, and the tweeters were then asked to actively search, think up, and share tips and guidance with non-tweeters. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The ground-up approach of the scale allows users to freely describe their experience rather than having to evaluate their responses against a ready-set frame. The scale has been used earlier in [27].…”
Section: Perceived Health Behavior Change (Phbc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The ground-up approach of the scale allows users to freely describe their experience rather than having to evaluate their responses against a ready-set frame. The scale has been used earlier in [27].…”
Section: Perceived Health Behavior Change (Phbc)mentioning
confidence: 99%
“…Of the total sample of 58 participants 33 were female, 25 male. Average age for the whole sample was 24 years (median 23), average for females being 24 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) min/max, median 22) and for males 23 (18-33 min/max, median 23). Eight participants reported that they do not usually play any computerized games, 19 used a computer as their main gaming platform, 20 used a gaming console, and 11 reported a mobile device as their primary gaming platform.…”
Section: Sample Characteristicsmentioning
confidence: 99%